Students’ common errors in quadratic equations: Towards improved mathematics performance - Gilbert Gumarao Baybayon; Minie Rose Caramoan Lapinid (IKIP Siliwangi and I-MES, 2024)
With the aim to close the performance gap between the high performing and the low performing students, this descriptive qualitative study was conducted to analyze students’ common and persisting errors in quadratic equations. Forty-six (N=46) Grade 9 students in a public high school in the Philippines participated in the study. Homework was given where students received instructions from video recordings and other online learning materials using blended learning. The common errors students committed were not following directions, mishandling signs, difficulty in recognizing a quadratic equation, inability to distinguish between solving a quadratic equation and simplifying an algebraic expression, failure to express quadratic equations in standard form, disregarding the negative roots, computational errors in basic algebraic conventions in simplifying radical and rational expressions, factoring, performing special products, and in completing the square. Students were interviewed to validate the error analysis. Immediate feedback through a whole class discussion was conducted the following day to discuss the errors and mistakes committed by students in order to address these and help them learn the necessary concepts and skills in quadratic equations. Instructional strategies and interventions for teaching quadratic equations are recommended for future studies.